Profil Kadar Enzim Serum Glutamat Piruvat Transaminase (SGPT) dan Serum Glutamat Oksaloasetat Transaminase (SGOT) Mencit Model Diabetes Melitus Pasca Pemberian Ekstrak Kulit Batang Cinnamomum burmanii - Abdul M Ukratalo (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Diabetes mellitus is a chronic metabolic disease characterized by hyperglycemia. Prolonged hyperglycemia leads to oxidative stress, which plays a crucial role in causing further complications, including liver damage characterized by increased levels of Serum Glutamate Pyruvate Transaminase (SGPT) and Serum Glutamate Oxaloacetate Transaminase (SGOT). This study aimed to examine the effects of Cinnamomum burmanii bark extract on SGPT and SGOT levels in a mouse model of diabetes mellitus. The research employed an experimental design using a completely randomized design. It consisted of five treatment groups: K- (normal mice), K+ (diabetic mice), P1, P2, and P3 (diabetic mice treated with Cinnamomum burmanii bark extract at doses of 125, 250, and 500 mg/kg BW). Streptozotocin was injected into groups K+, P1, P2, and P3 at a dose of 0.1 ml per mouse for 14 days. If blood glucose levels increased, extracts were administered to groups P1, P2, and P3 according to the predetermined doses for 14 days. On day 28, surgery was performed to collect blood serum for SGPT and SGOT analysis.. The results of the study indicated that Cinnamomum burmanii bark extract could reduce SGPT and SGOT levels in the diabetic mouse model. This demonstrates the potential of Cinnamomum burmanii as a therapeutic agent that may help reduce liver damage often observed in diabetes mellitus